Transformation and crisis of the school: Some reflections on the Colombian case - Palacios Mena, Nancy (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
The school is not any more a development institution for excellence and what sets out the ideal of education is not necessarily what happens in educational establishments, the relationship between the concepts and working ways of the discipline, the rule and democracy are the keys to the social organization of the institutions: because those where there is a relative coherence between discourse and practice and clarity in the essential approaches that underlie its operation, they have a greater capacity to resolve conflicts that may arise between the actors in their interior relate. In this inception, the school was conceived as an institution that should ensure simultaneously the integration into the society and the promotion of the individual. This school model was characterized by a set of principles and values designed as sacred, that also they did not have for what being well-taken. The changes in the society, the introduction of new ideologies and life styles, as well as changes in the way of being related, of acting and of thinking about the members of the same school, the diversification of the school offer, the multiplication of establishments, the overcrowding of the education, the differences in the way of thinking and of acting of the teaching students, and managing personnel of the institutions, they did that beginners in structuralism who sustain the school institution today are perceived as uncertain and contradictory. The functions of the school have been dismantled and the social utility of the studies, its cultural purposes and its ways of control are not already shared for whom they coexist in the schools, thus the changes that have happened in last decades in the social organization of the school and so, in the relations between its members, take part of a way of working in which it is already it cannot be conceived as a unified system, but as a space where there are differences and convergences between its members, specifically in the way of thinking as in that of acting.